Composition of Government Expenditure, Human Capital Accumulation, and Welfare - Matovu, John. (Washington, D.C. : International Monetary Fund, 2000)
This paper uses a dynamic general equilibrium model calibrated to Ugandan data to examine the welfare effects of alternative scenarios of government expenditure and tax financing. Two expenditure types are considered: social spending that affects human capital, and infrastructure expenditures that affect productivity. The paper finds that social expenditures lead to higher economic growth depending on the form of financing; young generations benefit most from social spending financed by consumption taxes; agents do not substitute between human and physical capital as a result of changes in expenditure composition; and improving the productivity of fiscal expenditure is both growth and welfare enhancing.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet